Flexible Electroactive Nanomaterials Biotemplated with Versatile M13 Phage Platforms1. Issue 10 (22nd May 2013) - Vera‐Robles, Liliana Irais; Van Tran Nhieu, Guy; Laberty‐Robert, Christel; Livage, Jacques; Sanchez, Clement
<x xml:space="preserve">Abstract</x> Producing electrodes for methanol oxidation using M13 phage as a new support are designed. This electrode shows electroactivity because the M13 phage can direct the size of the metal nanoparticles (NPs) allowing it a good dispersion, building a 3D network. This nanoarchitecture reduces poisoning on the surface of the NPs keeping the electroactivity <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>